Guest Editorial Column - Kondratenko, Yuriy P.; Mokhor, Volodymyr V. (Journal of Mobile Multimedia, 2021)
Dear Readers, We are very glad to introduce you to this Special Issue of the Journal of Mobile Multimedia “Mobile Communication and Computing for Internet of Things and Industrial Automation”. This Special Issue is published in collaboration with authors from research institutions and universities who have great experience in the development of international research projects on Internet of Things, industrial automation, robotics, soft computing, gesture communications and mobile multimedia. The aim of this Special Issue is to present the systematized research, description and analysis of new theoretical results and applications of mobile technologies for industrial and special robots, control systems, communications, data transmission and education. The Special Issue consists of four articles: The article “Inspection Mobile Robot’s Control System with Remote IoT-based Data Transmission”, by Y. Kondratenko et al., is devoted to the remote-control system for the mobile inspection robot operating on inclined ferromagnetic surfaces. The focus is on the control system’s architecture and remote data transmission based on IoT technologies. The proposed system makes it possible to control the robot’s movement along surfaces in different ......